Giant valley splitting in a MoTe2/MnSe2 van der Waals heterostructure with room-temperature ferromagnetism. Issue 6 (25th February 2022) - Li, Qianze; Zhang, Cai-xin; Wang, Dan; Chen, Ke-Qiu; Tang, Li-Ming
Abstract : The Curie temperature increases from an intrinsic value of 266 K to 353 K when the biaxial tensile strain of 2.3% is applied to the monolayer MnSe2 magnetic substrate, but the valley splitting of MoTe2 remains as large as 72 meV. Abstract : An intrinsic large valley splitting has been realized in van der Waals (vdW) heterostructures formed by monolayer MoTe2 and layered room-temperature ferromagnetic MnSe2 via first-principles calculations. The value of valley splitting of MoTe2 can reach 106 meV among a variety of stacking MoTe2 /MnSe2 heterobilayers, which is equivalent to the effective Zeeman splitting in an external magnetic field of 530 T. And the magnitude of valley splitting can be further enhanced by applying external vertical-stress and biaxial compressive strain. To obtain a higher operating temperature, a biaxial tensile strain of 2.3% has been applied on the monolayer MnSe2 magnetic substrate, and the corresponding Curie temperature increased from an intrinsic value of 266 K to 353 K, but the valley splitting can still remain as large as 72 meV. This means that we can strike a balance between large valley splitting and high Curie temperature, which is vital for the application of magnetic valley electronic devices.